Characterization of the reward structural connectivity in female Malay adolescents using diffusion magnetic resonance imaging - Zabri, Siti Hajar (2021)
Introduction: The reward network is highly investigated as it is known to be involved in substance addiction and reward sensitivity. Adolescents have been shown to be more reward sensitive compared to other age groups. Previous studies have also shown that the white matter tracts between the frontostriatal reward-related brain regions was associated with reward sensitivity. Objective: Since the reward network of female Malaysian Malay adolescents is understudied, the aim of this study was to characterize the white matter structural connectivity of the frontostriatal reward circuit of 15 healthy female Malaysian Malay adolescents by determining the relative connection probability of nucleus accumbens (NAcc) seed region to amygdala, anterior cingulate cortex (ACC), medial orbitofrontal cortex (mOFC), hippocampus, ventrolateral prefrontal cortex (vlPFC) and dorsolateral prefrontal cortex (dlPFC). This study also investigated the pattern of distribution from the parcellation of the NAcc corresponding to the connectivity of the 6 targets. Methodolgy: Diffusion magnetic resonance imaging (dMRI) was used to study the reward structural connectivity via probabilistic tractography which was performed for each subject by calculating the number of streamlines between the seed (NAcc) and each target mask (amygdala, ACC, mOFC, hippocampus, vlPFC and dlPFC). Results: The result showed that the sample with typical reward responsiveness for healthy participants had significantly the highest relative connection probability of NAcc to mOFC, while the NAcc parcellation showed the widest distribution of connection to mOFC compared to the other 5 targets in both sides of the brain. Conclusion: Both of these findings support that NAcc and mOFC have the highest connection strength compared to the 5 targets. This supports previous study that shows NAcc is highly specific to the connection to mOFC. This finding can be explained by prior evidence showing early maturing of the NAcc-mOFC tract.